2018
DOI: 10.1111/ajt.14691
|View full text |Cite
|
Sign up to set email alerts
|

Incidence, characterization, and impact of newly detected donor-specific anti-HLA antibody in the first year after pediatric heart transplantation: A report from the CTOTC-04 study

Abstract: Data on the clinical importance of newly detected donor-specific anti-HLA antibodies (ndDSAs) after pediatric heart transplantation are lacking despite mounting evidence of the detrimental effect of de novo DSAs in solid organ transplantation. We prospectively tested 237 pediatric heart transplant recipients for ndDSAs in the first year posttransplantation to determine their incidence, pattern, and clinical impact. One-third of patients developed ndDSAs; when present, these were mostly detected within the firs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
27
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 33 publications
1
27
0
Order By: Relevance
“…Studies in adults have shown that the presence of de novo DSAs can accelerate graft vasculopathy and decrease graft survival in heart and other solid organ transplants, with smaller studies in the pediatric heart transplant population yielding similar results . Our findings of more frequent rejection episodes in patients with newly detected DSAs are consistent with prior studies, including one that showed DSA‐positive pediatric cardiac transplant patients had 2.5 times more rejection events per year than DSA‐negative patients and a more recent study showing that newly detected DSAs in the first year post‐transplant are associated with more cellular rejection episodes . In one of the studies, patients with DSAs also had higher rates of CAV and decreased 5‐year graft survival .…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Studies in adults have shown that the presence of de novo DSAs can accelerate graft vasculopathy and decrease graft survival in heart and other solid organ transplants, with smaller studies in the pediatric heart transplant population yielding similar results . Our findings of more frequent rejection episodes in patients with newly detected DSAs are consistent with prior studies, including one that showed DSA‐positive pediatric cardiac transplant patients had 2.5 times more rejection events per year than DSA‐negative patients and a more recent study showing that newly detected DSAs in the first year post‐transplant are associated with more cellular rejection episodes . In one of the studies, patients with DSAs also had higher rates of CAV and decreased 5‐year graft survival .…”
Section: Discussionsupporting
confidence: 89%
“…21,22 Our findings of more frequent rejection episodes in patients with newly detected DSAs are consistent with prior studies, including one that showed DSA-positive pediatric cardiac transplant patients had 2.5 times more rejection events per year than DSA-negative patients and a more recent study showing that newly detected DSAs in the first year post-transplant are associated with more cellular rejection episodes. 24,26 In one of the studies, patients with DSAs also had higher rates of CAV and decreased 5-year graft survival. 24 Another study also showed that the appearance and persistence of de novo antibodies after the first year were associated with reduced graft and patient survival.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, in most of the available studies, results were not reported separately for adult and pediatric patient . Evidence from pediatric kidney and heart transplantation showed that DSA is a risk factor for mortality and acute or chronic rejection . Dipchand et al have recently shown in a multicenter study including 237 pediatric heart‐transplant patients that one‐third of patients developed de novo DSA, usually within 6 weeks after transplantation, and that DSA were a risk factor for acute cellular rejection in the first year posttransplantation.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence from pediatric kidney and heart transplantation showed that DSA is a risk factor for mortality and acute or chronic rejection . Dipchand et al have recently shown in a multicenter study including 237 pediatric heart‐transplant patients that one‐third of patients developed de novo DSA, usually within 6 weeks after transplantation, and that DSA were a risk factor for acute cellular rejection in the first year posttransplantation. Similarly, Irving et al showed that 40% of pediatric heart‐transplant patients developed de novo DSA and that patients with persistent vs. transient DSA showed an increased incidence of CAV, rejection and graft loss.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, in a prior analysis from our study we found that ventricular assist device (VAD) implantation was associated with a lower risk of developing newly detected donorspecific anti-HLA antibodies, suggesting the relationship of sensitizing events to outcomes in children may differ from that reported in adults. 9 When one examines readmission within 1 year of initial hospital discharge, there are several factors that are strongly associated with the incidence of readmission. A longer duration of initial hospital admission is associated with a higher readmission rate.…”
Section: Discussionmentioning
confidence: 99%